Factors Influencing Consumer Buying Behaviour Of Luxury Fashion Brands in Malaysia - Seilkhanova, Saniya (2017)
Today luxury fashion brands are commonly purchased by the Malaysian consumers and they have a tendency to wear such brands since those brands may display their identity and social position. Malaysia has the highest growth rate score across all South-East Asian countries and the percentage of luxury consumption in Malaysia has increased significantly. This dissertation will investigate consumers’ purchase desire and intention toward middle-class luxury fashion brands in Malaysia, with the use of personal values and some external factors. Numerous studies have been conducted concerning purchase behaviour of consumers, however little research has been done concerning purchase intention of Malaysian consumers toward luxury fashion brands. In this research, personal values that have been involved to predict consumers’ intention to purchase middle-class luxury fashion brands include need for conspicuousness, need for materialism, and need for uniqueness. In addition, more specific factors such as fashion innovativeness and fashion involvement were added to this study. In this study, online survey and questionnaires were conducted as a main research method in order to find out motivating factors behind their luxury purchase intention. Quantitative research using 250 internet surveys was implemented involving local and international students, and university’s staff, mostly aged between 19-69 years. Further snowball and convenience sampling methods were employed in this study.